Dental health of children with autism spectrum disorder: significance of salivary pH and dental visits on DMF-T index: Kesehatan gigi anak autism spectrum disorder: signifikansi pH saliva dan kunjungan dokter gigi terhadap indeks DMF-T - Syahrir, Syakriani; Kurnia, Stifan Dwi; Ansar, Mahdiyyah Mufadhdhal; Yunus, Aisyah Khairunnisa (Makassar Dental Journal, 2025)
This study aimed to analyse the relationship between various caries risk factors and DMF-T status in children with autism spec-trum disorders (ASD). The study was conducted cross-sectionally on 56 students at Yayasan Darul Fikri Makassar from Janua-ry to May 2024. Data were collected through clinical examination, salivary pH measurement, and questionnaires related to dental care behaviour and food consumption. Data analysed using the chi-square test showed a significant relationship between sali-vary pH and regular visits to the dentist with DMF-T status (p<0.05), while socioeconomic factors, sugar consumption, brushing frequency, and fluoride toothpaste use did not show a significant relationship. It was concluded that salivary pH and regular den-tal visits are important in caries prevention in ASD children.